Physical-chemical Properties of Aqueous TBAOH Solution for Gas Hydrates Promotion. (2016) - Nashed, Omar; Koh, Josephine Chin Hui; Lal, Bhajan
Abstract: Gas hydrates attract the attention of many industries for various potential applications such as gas separation and storage. To industrialize the gas hydrate technology, rapid hydrate formation at mild conditions is crucial. Chemical additives such as ionic liquids were investigated for hydrate promotion. The knowledge of physical-chemical properties of ionic liquids is crucial in development of gas hydrate technology in industry as these fundamental properties determined the hydrate formation rate. This work measures the density, pH, electrical conductivity, and surface tension of aqueous tetrabutylammonium hydroxide solutions. The concentrations were chosen to cover the common hydrate promotion range of 0.001-10 wt%. The results showed high dependence of the studied properties on the concentration. pH and electrical conductivity were increased with increase of TBAOH concentration conversely to density and surface tension. The amount of CO2 consumed to form the hydrate was measured at a pressure of 35 bar and a temperature 274.15. Significant increase of CO2 consumption in the presence of TBAOH solutions was observed. However, as the concentration increased, more CO2 was consumed.